SYARI'AH OPTIMIZATION OF BUSINESS THEORY IN PREVENTING RIBA PRACTICES IN MURABAHAH CONTRACT (Case Study at Muamalat Indonesian Bank) - Muchlis, Saiful; Sukirman, Anna Sutrisna; Irmawati, Irmawati (IJIBE (International Journal of Islamic Business Ethics), 2019)
This study aims to (1) determine the determination of the murabahah contract margin from the Asset /Liability Management Committee (ALCO) perspective, (2) know the Shari’ah Enterprise Theory (SET) approach in realizing the murabahah contract margin system in accordance with sharia principles. This research is a qualitative research using an interpretive paradigm with a phenomenological approach that takes the location of research at Bank Muamalat Indonesia. Data collection was carried out using the interview method with informants and some other secondary supporting data obtained from the entity’s official website. The data management and analysis techniques are carried out through three stages, namely through data reduction, data presentation and conclusion drawing (verification). The results of the research show that the implementation of the Murabahah contract margin system at Bank Muamalat Indonesia is considered not to have fully implemented the sharia concepts and principles. This is because the ALCO Team is still based on the BI (Bank Indonesia) rate so that the determination of margins is still in accordance with the prevailing interest rates at Bank Indonesia. Thus, it can be said that Bank Muamalat still contains elements of usury because it makes BI interest rates as a material consideration in determining the applicable margin in Islamic banks. So that SET is considered able to realize the murabahah contract margin system because it contains the values of justice, truth, honesty, trustworthiness and accountability and is expected to complement or improve the margin system of the murabahah agreement to conform to the actual sharia principles.